Establishing cooperation between groups: Ingroup versus outgroup punishment - Christian Stoff (University of Zurich, Socioeconomic Institute, 2006)
We analyse interethnic cooperation in an infinitely repeated prisoner's dilemma when members of one group are unable to target punishment towards individual defectors from the other group. We first show that indiscriminate outgroup punishment may sustain cooperation in this setting. Our main result, however, is that the introduction of ingroup punishment in addition to outgroup punishment represents a better sanctioning institution in the sense that cooperative outcomes may persist in situations where outgroup punishment alone fails to induce cooperation. Our findings are consistent with historical evidence on the dynamics of interethnic conflicts.
Keywords: C70; C72; O12; O17; Z13; 330; Interethnic conflicts; Interethnic cooperation; Ethnicity; Intergroup relations; Ingroup punishment; Outgroup punishment; Ethnische Diskriminierung; Ethnische Gruppe; Kollektives Handeln; Gefangenendilemma; Spieltheorie; Ethnische Beziehungen